Awakening Neuropsychiatric Research Into the Stria Medullaris: Development of a Diffusion-Weighted Imaging Tractography Protocol of This Key Limbic Structure - Roddy, Darren W.; Roman, Elena; Rooney, Shane; Andrews, Sinaoife; Farrell, Chloe; Doolin, Kelly; Levins, Kirk J.; Tozzi, Leonardo; Tierney, Paul; Barry, Denis; Frodl, Thomas; O’Keane, Veronica; et al. (Frontiers in Neuroanatomy, 2018)
The Stria Medullaris Thalami is a discrete white matter tract that directly connects frontolimbic areas to the habenula, allowing the forebrain to influence midbrain monoaminergic output. Habenular dysfunction has been shown in various neuropsychiatric conditions. However, there exists a paucity of research into the habenula’s principal afferent tract, the stria medullaris. Diffusion-weighted tractography may provide insights into the properties of the stria medullaris in vivo, opening up investigation of this tract in conditions of monoamine dysregulation such as depression, schizophrenia, addiction, and pain. We present a reliable method for reconstructing the stria medullaris using diffusion-weighted imaging, and examine the effects of age and gender on tract diffusion metrics. We also investigate reproducibility of the method through inter-rater comparisons. In consultation with neuroanatomists, a Boolean logic gate protocol was developed for use in ExploreDTI to extract the stria medullaris from constrained spherical deconvolution based whole brain tractography. Particular emphasis was placed on the reproducibility of the tract, attention to crossing white matter tract proximity and anatomical consistency of anterior and posterior boundaries. The anterior commissure, pineal gland and mid point of the thalamus were defined as anatomical fixed points used for reconstruction. Fifty subjects were scanned using High Angular Resolution Diffusion Imaging (61 directions, b-value 1500 mm3). Following constrained spherical deconvolution whole brain tractography, two independent raters isolated the stria medullaris. Each output was checked, examined and cleaned for extraneous streamlines inconsistent with known anatomy of the tract by the rater and a neuroanatomist. A second neuroanatomist assessed tracts for face validity. The stria medullaris was reconstructed with excellent inter-rater reliability for dimensions and diffusion metrics. Gender had no effect on the dimensions or diffusion metrics, however radial diffusivity showed a positive correlation with age. Reliable identification and quantification of diffusion metrics of the stria medullaris invites further exploration of this key habenula linked structure in neuropsychiatric disorders such as depression, anxiety, chronic pain, and addiction. The accurate anatomical localization of the stria medullaris may also aid preoperative stereotactic localization of the tract for deep brain stimulation treatment.